Inovasi Media Pembelajaran Melalui Penggunaan Media Google Earth di SMA Negeri 1 Lamongan - Dimas, Firdan; Bagas, Aditya; Faiq, Ahmad (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2024)
This research aims to create a new innovation drive in geography learning, especially the remote sensing sub-chapter, for high school students in Lamongan City. The method we use in this research is quantitative with an experimental method carried out using observation, questionnaires, recording and testing data collection techniques. Along with the development of time and era, teachers are required to be able to understand technology and the surrounding environment in order to fully understand the developments that have occurred in the scope of remote sensing. Such as the use of smartphones and computers in data processing and developing teaching materials for students in Lamongan City, Google Earth is one application that can facilitate the development of teaching materials by teachers for students in the educational sphere. The results of this research can show that the use of digital media in geography learning has a great influence on learning outcomes obtained from aspects of the learning process such as time allocation and availability of infrastructure to support students' learning process.Penelitian ini bertujuan untuk dapat menciptakan sebuah dorongan inovasi baru dalam pembelajaran geografi terlebih sub bab penginderaan jauh pada siswa SMA di Kota Lamongan. Metode yang kami gunakan dalam penelitian ini adalah kuantitatif dengan metode eksperimen yang dilakukan dengan teknik pengumpulan data observasi, angket, pencatatan dan tes. Seiring dengan perkembangan waktu dan zaman yang mengharuskan guru untuk dapat memahami teknologi dan lingkungan sekitar agar dapat memahami penuh akan perkembangan yang telah terjadi dalam lingkup penginderaan jauh ini. Seperti penggunaan smartphone dan komputer dalam olah data dan pengembangan materi ajar untuk siswa di Kota Lamongan, Google Earth yang merupakan salah satu aplikasi yang dapat mempermudah pengembangan materi ajar oleh guru terhadap siswa di lingkup pendidikan. Hasil dari penelitian ini dapat menunjukkan bahwa penggunaan media digital dalam pembelajaran geografi sangat berpengaruh pada hasil belajar yang didapatkan dari aspek proses pembelajaran seperti alokasi waktu dan ketersediaan sarana prasarana dalam mendukung proses pembelajaran siswa.